2019
DOI: 10.1002/qj.3489
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the predictability of Medicanes in ECMWF ensemble forecasts using an object‐based approach

Abstract: The predictability of eight southern European tropical‐like cyclones – seven Medicanes and the first‐ever documented case of such a storm in the Bay of Biscay – is studied evaluating European Centre for Medium‐Range Weather Forecasts (ECMWF) operational ensemble forecasts against operational analysis data. Forecast cyclone trajectories are compared with the cyclone trajectory in the analysis by means of a dynamic time warping technique, which allows one to find a match in terms of their overall spatio‐temporal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 71 publications
6
15
0
Order By: Relevance
“…This indicates that other synoptic-scale aspects related to the PV streamer, for example uncertainty in its position, shape, or intensity, limited the predictability of the medicane (similar to Maier-Gerber et al, 2019, for a tropical transition over the North Atlantic). The existence of several "stages" in cyclone predictability is consistent with the systematic analysis of the predictability of recent medicanes by Di Muzio et al (2019), which showed that such "forecast jumps" occur with different lead times for different forecast parameters. For example, rapid increases in the probability of cyclone occurrence can be found with longer lead times (4-7 d before the mature phase of the medicane) than rapid decreases in the spread of cyclone position (2-5 d) and of the strength of the upper-level warm core (initializations after cyclogenesis).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates that other synoptic-scale aspects related to the PV streamer, for example uncertainty in its position, shape, or intensity, limited the predictability of the medicane (similar to Maier-Gerber et al, 2019, for a tropical transition over the North Atlantic). The existence of several "stages" in cyclone predictability is consistent with the systematic analysis of the predictability of recent medicanes by Di Muzio et al (2019), which showed that such "forecast jumps" occur with different lead times for different forecast parameters. For example, rapid increases in the probability of cyclone occurrence can be found with longer lead times (4-7 d before the mature phase of the medicane) than rapid decreases in the spread of cyclone position (2-5 d) and of the strength of the upper-level warm core (initializations after cyclogenesis).…”
Section: Introductionsupporting
confidence: 82%
“…According to the CPS (Fig. 3b), Zorbas formed as a cold-core cyclone and within 18 h acquired a deep warm core that was sustained for more than 3 d. This is comparable to the January 1982 case investigated by Picornell et al (2014) but substantially longer than for all eight recent medicane cases investigated by Di Muzio et al (2019) using the same dataset. Zorbas reached its maximum intensity (992 hPa) only 12 h after cyclogenesis.…”
Section: Synoptic Overviewsupporting
confidence: 73%
“…However, despite the scientific efforts emerging in a variety of sensitivity studies, even now NWP models suffer from a significant forecast skill reduction in the simulation of MTLCs, as they sometimes intensify the cyclone in an unrealistic way, or fail to foresee its development and evolution accurately. This predictability limitation depends on many factors and varies from case to case [13]. In some events, a large sensitivity to the location of the model domain and to the horizontal grid resolution [14] is observed, while in other cases parameterization schemes play a fundamental role [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers have clarified some peculiar aspects of Medicanes, from the mechanisms of development to their predictability [15], including the sensitivity of numerical simulations to different parameterization schemes. However, additional studies are necessary to provide a comprehensive picture for this particular category of cyclones.…”
Section: Discussionmentioning
confidence: 99%